Convergence of the right and left external jugular veins to the midline: a rare finding of anatomical variation - Guerra, Carolina Macedo (2024)
Venous blood from the head and neck are drained mainly by the internal and external jugular veins. The external jugular vein is located in the anterolateral region of the neck taking a complex pathway perpendicularly down the neck to join the subclavian vein, however, there can be anatomical variations that affect its course. To describe an anatomical variation in the left and right external jugular veins discovered during the dissection of a cadaver in Human Anatomy class. The present study is a case report describing an anatomical variation in the external jugular veins observed during a routine dissection for Human Anatomy class at the Faculty of Medical Sciences of Minas Gerais on an adult male cadaver of unknown age, preserved in formaldehyde solution. the dissection showed that the right and left external jugular veins converged toward the midline, joining just above the level of the jugular notch. Knowledge of variations in the neck superficial venous system is crucial to avoid complications from medical procedures. The present variation was not found described in the literature.